Efficacy and Safety of Ixekizumab Through 5 Years in Moderate-to-Severe Psoriasis: Long-Term Results from the UNCOVER-1 and UNCOVER-2 Phase-3 Randomized Controlled Trials - Craig Leonardi; Kristian Reich; Peter Foley; Hideshi Torii; Sascha Gerdes; Lyn Guenther; Melinda Gooderham; Laura K. Ferris; Christopher E. M. Griffiths; Hany ElMaraghy; Heidi Crane; Himanshu Patel; et al. (Adis, Springer Healthcare, 2020)
Abstract Introduction Ixekizumab, a high-affinity monoclonal antibody that selectively targets interleukin-17A, is approved for treatment of moderate-to-severe plaque psoriasis. Our objective was to evaluate the long-term efficacy and safety of ixekizumab in moderate-to-severe plaque psoriasis through 5 years. Methods Data were integrated from the UNCOVER-1 and UNCOVER-2, randomized, double-blinded, phase-3 trials. Patients who continuously received the labeled ixekizumab dose, were static Physician's Global Assessment (sPGA) (0,1) responders at Week 12 and completed 60 weeks of treatment could enter the long-term extension (LTE) period. Patients could escalate to every-2-week dosing per investigator opinion. Efficacy and health outcomes included proportion of patients achieving Psoriasis Area and Severity Index (PASI) 75/90/100, sPGA (0,1) and (0), absolute PASI ≤ 5/ ≤ 3/ ≤ 2/ ≤ 1 and Dermatology Life Quality Index (DLQI) (0,1). Results exclude patients who escalated to every-2-week dosing. A modified non-responder imputation method was used to account for missing data. Supplemental analyses include patients who escalated to every-2-week dosing and observed and multiple imputation results. Exposure-adjusted safety outcomes are also reported. Results Of 206 patients who entered the LTE periods, 172 completed treatment. At Week 60, PASI 75/90/100 responses were 94.7%, 85.0% and 62.1%, respectively, and at year 5 were 90.3%, 71.3% and 46.3%, respectively. Similarly, meaningful responses were achieved for the other efficacy and health measures. Among patients with PASI 100 through 5 years, 92% achieved DLQI (0,1), indicating no impact of skin disease on quality of life. During the LTE period, exposure-adjusted incidence rates were 31.4 per 100 patient-years for treatment-emergent adverse events and 6.8 per 100 patient-years for serious adverse events. No deaths were reported. No new or unexpected safety findings were noted. Conclusions The results demonstrate 80 mg ixekizumab maintains long-term efficacy and a safety profile consistent with previous data in patients with moderate-to-severe plaque psoriasis through 5 years of treatment. Trial Registration ClinicalTrials.gov identifier, UNCOVER-1: NCT01474512, UNCOVER-2: NCT01597245.